Conscience at war : the Israeli soldier as a moral critic - Linn, Ruth (SUNY series in Israeli studies., 1996)
A psychological study of the Intifada "refusers," focusing on the intellectual and moral challenges selective conscientious objection poses for resisters in Israel. Linn (School of Education, Haifa U.) uses the theories of Rawls, Walzer, Kohlberg, and Gilligan as a framework for understanding and interpreting interviews with objecting soldiers. Annotation copyright by Book News, Inc., Portland, OR.